Associations of continuity and coordination of care with outcomes and costs after discharge among patients with heart failure: A nationwide population-based study. (15th April 2022) - Chang, Guann-Ming; Chen, Jau-Yuan; Kuo, Wen-Yu; Tung, Yu-Chi
Abstract: Background: Although continuity and coordination of care have received increased attention as important ways to improve outcomes and decrease costs, limited information is available concerning the effects of "care continuity" and "care coordination" on mortality and costs. We used nationwide population-based data from Taiwan to explore the effects of care continuity and coordination on mortality and costs for heart failure. Methods: We analyzed all 18, 991 heart failure patients 18 years of age or older and discharged from hospitals in 2016 using Taiwan's National Health Insurance claims data. Cox proportional hazard and multiple linear regression models were used, after adjustment for patient characteristics, to explore the relative impacts of the continuity of care (COC) index and care density on 1-year mortality and costs. Results: Higher COC index was associated with lower mortality (low vs. medium: hazard ratio [HR], 1.59; 95% confidence interval [CI], 1.47–1.71; high vs. medium: HR, 0.66; 95% CI, 0.61–0.72) and costs (low vs. medium: cost ratio [CR], 1.11; 95% CI, 1.07–1.16; high vs. medium: CR, 0.84; 95% CI, 0.81–0.88). Low care density was associated with higher mortality (low vs. medium: HR, 1.12; 95% CI, 1.04–1.20). Higher care density was associated with lower costs (low vs. medium: CR, 1.14; 95% CI, 1.10–1.18; high vs. medium: CR, 0.76; 95% CI, 0.73–0.79). Conclusions: Low care continuity and coordination are associated with higher 1-year post-discharge mortality and costs. Facilitating care continuity and coordination may be an important strategy for improving value-based care for heart failure. Highlights: Higher continuity of care is associated with lower 1-year mortality and costs for discharged patients with HF. Low care coordination is associated with higher 1-year post-discharge mortality and costs. Facilitating care continuity and coordination may be an important strategy for improving value-based care for HF.